(untitled) (MAUSAM, 2007)
This paper investigates the spatial distribution of precipitable water contents over Indian region for the southwest monsoon 2005. The precipitable water contents are derived from the objective analysis field of operational Numerical Weather Prediction system of India Meteorological Department. The study shows that the distribution of PWC is capable to capture large scale features of monsoon precipitation system. Real-time availability of this product is expected to be useful in monitoring and prediction of heavy rainfall events.